Pengembangan E-Modul Fisika Berbasis Problem-Based Collaborative Learning Untuk Meningkatkan Sikap Ilmiah dan Prestasi Belajar Siswa - I N. Widya Artha; I Gde Wawan Sudatha; I Kadek Suartama; I Made Tegeh; I Wayan Sukra Warpala (Jayapangus Press, 2026)
This study aimed to develop a PBCL-based CoLearn Physics E-Module integrated with PhET simulation on Projectile Motion and to evaluate its validity, practicality, and effectiveness in improving students’ scientific attitudes and learning achievement. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The participants included two subject matter experts, two instructional media experts, two instructional design experts, two physics teachers, and 36 eleventh-grade students of SMAK Harapan. Data were collected using validation sheets, practicality questionnaires, scientific attitude questionnaires, and learning achievement tests. Product effectiveness was examined using a one-group pretest-posttest design and analyzed through paired sample t-test, N-gain, and Cohen’s d. The results indicated that the developed E-Module achieved a very good category based on expert validation, with scores of 81% from subject matter experts, 92% from instructional media experts, and 94% from instructional design experts. The practicality test showed that the E-Module was categorized as highly practical based on teacher assessment (90.00%), individual trials (86.00%), small-group trials (87.80%), and large-group trials (88.72%). The paired sample t-test revealed significant differences between pretest and posttest scores in scientific attitudes (t(35) = -18.260; p < 0.001) and learning achievement (t(35) = -10.051; p < 0.001). The N-gain values were in the moderate category for scientific attitudes (0.33) and learning achievement (0.51), while Cohen’s d indicated large effect sizes for scientific attitudes (1.15) and learning achievement (2.46). Therefore, the PBCL-based CoLearn Physics E-Module integrated with PhET simulation is considered valid, highly practical, and effective for supporting physics learning on Projectile Motion.